Entrepreneurship of Raudhatul Ulum Islamic Boarding School on Community Welfare Maqashid Sharia Perspective - Zaid, Muhammad; Fadil Sj; Aunur Rofiq (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article will discuss Islamic boarding schools which were initially as centers for Islamic studies and then innovated as social economic centers by developing entrepreneurship in Islamic boarding schools and then analyzing them from the perspective of sharia maqashid. This research is a qualitative research, with the type of field research (field research). The data sources in this study consist of two data sources, namely primary data and secondary data. Using three data collection techniques: Observation, interview, and observation. The results of the study show that the Raudhatul Ulum Islamic Boarding School has played a dual role, both as an Islamic educational institution and as an economic role in improving the welfare, both internal and external of the Islamic boarding school by operating and developing Islamic boarding school business units in various fields such as trade, services, agriculture, and religious tourism. And it can be concluded that the entrepreneurship applied by the Raudhatul Ulum Islamic Boarding School to the welfare of the community has fulfilled the five principles of maqasid sharia or commonly known as kulliyat al-khamsah (five general principles). The five maqashids are: hifdzu din (maintaining religion), hifdzu nafs (maintaining the soul), hifdzu 'aql (maintaining the mind), hifdzu maal (maintaining property), and hifdzu nasab (maintaining offspring).